Assessment of Topographic Memory in Mice in a Complex Environment Using the Hamlet Test. Issue 2 (25th May 2018) - Crouzier, Lucie; Maurice, Tangui
Abstract: Here we provide instructions to measure topographic memory in mice using the Hamlet test, a complex environment. The apparatus mimics a small hamlet with a central agora and five houses, which are functionalized since mice can drink, eat pellets, hide within a small maze, run in an activity wheel, or interact with a stranger mouse behind a grid. The houses are interconnected through a network of streets in a five‐arm star shape, and a video tracking system takes information from the activity in each house or follows a single mouse by trajectometry. Training the mice in the Hamlet, in groups for several hours per day over several days or weeks, allows consolidation of topographic memory (i.e., route learning involving both allocentric and egocentric strategies). Analysis of topographic memory can be performed a posteriori in a probe test by depriving mice of water or food and measuring their ability to efficiently reach the "eat" or "drink" house. Control groups include mice tested in non‐deprived condition and mice naïve to the Hamlet and tested in deprived or non‐deprived conditions. The present article details the apparatus, procedures, and protocols that can be used to reliably habituate mice in this complex environment and measure topographic memory. © 2018 by John Wiley & Sons, Inc.